Geopolitik Israel dan Palestina: Studi Kosakata Geopolitik dalam Penerjemahan Bebas pada Teks Berita Ketegangan Israel dan Palestina di Situs Al-Jazeera - Nisa, Mauidlotun; Novianti, Putri Ninda (Jurnal Penerjemahan, 2023)
This study aims to reveal the meaning of Israeli and Palestinian Geopolitical vocabulary in the translation of Israeli and Palestinian tension news in Al-Jazeera Arabic news in 2021 because Al-Jazeera is one of the most popular news sites as a representation of Middle Eastern and Western media. This study is qualitative research with a geopolitical approach and free translation theory. The data for this article are five Al-Jazeera news texts about Israeli and Palestinian tensions. The secondary data of this research are relevant Indonesian news such as from tribun news, liputan6.com, tempo.co, sindonews, kumparan.com, republika.co.id, BBC Indonesia, detik.com, hidayatullah.com, kontan.co.id, kompas, CNBC Indonesia, net news, and merdeka.com. This study found the meaning of geopolitical vocabulary that is important for a translator to know, such as ُُتا َض َوا ُُي ِل ْيِئا َر ْس ِ ْلْاُ َف ُملا 'negotiation', ُُي ِل َو ُّدلا ُ ُش ْي َجلا ‘Israel Defense Forces (IDF)’, ا ُُيِ ن ْي ِط ْس َل ِفلا ُي ِل ْيِئا ِ ْلْا ُ ُعا َر ْس َ ْلْا ُ ن ْم ُس ِل ْج َم ‘UN security council’,ُ َفا َه َلاُُ ‘Lehava’, ُُ ب ْي ِ ب َ ُ ْلَ ت 'Tel Aviv', and ر ِ صلا 'Israel Palestine conflict'. The translation of Al-Jazeera's texts about the Israeli-Palestinian conflict must be supported by geopolitical knowledge between the two countries. The better the geopolitical understanding, the better the translation quality. Keywords: Al-Jazeera News, Geopolitics, Translation, Conflict, Israel and Palestine.